Development of guidelines reality group counseling-based on cyber counseling to increase student adversity quotient - Taneo, Joris; Malelak, Erly Oviane; Loban, Maria Natalia; Bait, Dayana Adrela (Universitas Negeri Padang, 2022)
Adversity quotient is the ability of individuals to face various difficulties and make it an opportunity to achieve their goals. Adversity quotient can be changed or enhanced, so it is not a permanent personality. Cyber counseling based on reality group counseling can be one of the efforts to increase the adversity quotient of students. This study aims to produce Guidelines of Reality Group Counseling-Based on Cyber Counseling to Increase Student Adversity Quotient and see how effective it is. The research method is Research and Mevelopment. This guide consists of several components, and the feasibility of the guide was validated by 2 expert validators and 2 practitioner validators. Reality group counseling-based on cyber counseling to increase student adversity quotient is effective to increase the adversity quotient. This conclusion is based on pre-test and post- difference test scores, where there is an increase in the adversity quotient of students before and after the implementation of cyber counseling-based reality group counseling.